An interesting case of genital infantile hemangioma - Mahmood, Shafqat; Naeem, Muhammad (International Journal of Research in Medical Sciences, 2023)
Vascular lesions are commonly seen in newborns. They may be present at birth or appear in the days, weeks or months that follow. Most are benign and self-limiting but rarely they may be part of complex syndromes or systemic disorders, or they may be associated with complications requiring treatment. This is a case of a 2-month-old baby presenting with an Infantile hemangioma in the genital region.